Complete synchronization of a novel 6-D hyperchaotic Lorenz system with known parameters - S. Al-Obeidi, Ahmed; Fawzi AL-Azzawi, Saad (International Journal of Engineering and Technology, 2019)
There has been an increasing interest in field of high-dimensional systems and their synchronization phenomena. This paper deals with complete synchronization between two identical 6-D hyperchaotic Lorenz systems based on nonlinear control strategy. The designed control functions for the synchronization between the drive and response systems are succeed to achieve complete synchronization with the states of both systems are measurable and the parameters are known. Numerical simulations have verified the analytical synchronization technique.Â Â Â